Возможности колоэзофагопластики у детей раннего возраста - Иванов, Андрей Петрович; Кузьминых, Светлана Валерьевна; Подкаменев, Александр Владимирович; Ти, Роман Андриянович; Сырцова, Арина Родионовна; Мурашова, Ольга Александровна (Children’s Medicine of the North-West, 2021)